2016
DOI: 10.1080/08958378.2016.1224956
|View full text |Cite
|
Sign up to set email alerts
|

A scattering methodology for droplet sizing of e-cigarette aerosols

Abstract: Context: Knowledge of the droplet size distribution of inhalable aerosols is important to predict aerosol deposition yield at various respiratory tract locations in human. Optical methodologies are usually preferred over the multi-stage cascade impactor for high-throughput measurements of aerosol particle/droplet size distributions. Objective: Evaluate the Laser Aerosol Spectrometer technology based on Polystyrene Sphere Latex (PSL) calibration curve applied for the experimental determination of droplet size d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…1C). This is consistent with particle size determinations of e-cig vapors that were characterized by other methods and found to be in this range (57,64). Nicotine solution in saline has also been shown to generate droplets in the respirable diameter range (64,65).…”
Section: L95supporting
confidence: 87%
“…1C). This is consistent with particle size determinations of e-cig vapors that were characterized by other methods and found to be in this range (57,64). Nicotine solution in saline has also been shown to generate droplets in the respirable diameter range (64,65).…”
Section: L95supporting
confidence: 87%
“…Atmospheric aerosols affect the radiative balance of planet Earth (e.g., Ramanathan et al, 2001): directly by absorbing and scattering the sunlight (e.g., Schwartz, 1996) and indirectly through modifying the microphysical properties of the clouds (e.g., Lohmann and Feichter, 2005). The current state of the scientific knowledge of the total (direct and indirect) aerosol effect is still considered low due to the complexity of these effects (IPCC, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is no single instrument that could satisfy all these requirements: therefore, a combination of techniques has to be used to obtain accurate measurements of e-cigs aerosol size. Several approaches exploiting different experimental techniques were applied including optical transmission (Ingebrethsen, Cole, and Alderman 2012) and laser scattering (Cabot et al 2013;Pratte, Cosandey, and Goujon-Ginglinger 2016;Dunkhorst et al 2018), differential (electrical) mobility real-time (Ingebrethsen, Cole, and Alderman 2012;Fuoco et al 2014;Marini et al 2014;Manigrasso et al 2015;Mikheev et al 2016;Baassiri et al 2017;Scungio, Stabile, and Buonanno 2018) and scanning mobility near real-time (Zhang, Sumner, and Chen 2013;Fuoco et al 2014;Zhao et al 2016) methods, and inertial impaction (Alderman et al 2015;Baassiri et al 2017;Oldham et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the extreme sensitivity of e-cig aerosol/ vapor to a residence time it is also of a critical importance to understand how a piston pull-push based smoking machine may affect aerosol size in comparison with the smoking machine that provides direct smoke delivery from the e-cig outlet to analysis. A recent study measured highly diluted (1/10,000) e-cig aerosol using laser optical scattering (Pratte, Cosandey, and Goujon-Ginglinger 2016) and showed that applying a piston pull-push approach (increasing aerosol residence time by $3.4 s) led to a moderate particle size increase in comparison with direct push aerosol method for analysis. More studies are required to analyze the effect of residence time at low sample dilution and using alternative aerosol size measurements techniques, therefore a study of the influence of different types of the smoking machines on the particle size distribution was the third goal of this study.…”
Section: Introductionmentioning
confidence: 99%